Evolution of pancreaticoduodenectomy in the surgical treatment of chronic pancreatitis - Pereira-Lima, Luiz; Miguel, Pablo (Cirugía del Uruguay, 1989)
The author does an overview of the indications and severa! techniques of pancreatoduodenectomy in the treatment of pain in chronic pancreatitis. Eventually this operation, Speccially in chronic pancreatitis, presents technical dificulties and a severa! of post-operativa eomplications. Thus the authors suggest that pancreatoduodenectomy for chronic pancreatitis should be an operation for a reference center in, terested in the development of pancreatic surgery.